2013
DOI: 10.1111/pme.12183
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden of Opioid-Related Poisoning in the United States

Abstract: Opioid-related poisoning causes a substantial burden to the United States each year. Costs related to mortality account for the majority of costs. Interventions designed to prevent or reverse opioid-related poisoning can have significant impacts on cost, especially where death is prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 27 publications
1
59
0
Order By: Relevance
“…A final group of 16 publications were selected for inclusion in the report. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The two primary reasons for exclusion were an abuse treatment focus (15) and lack of cost data (12). A CASP checklist was completed for these 16 publications to assess quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A final group of 16 publications were selected for inclusion in the report. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The two primary reasons for exclusion were an abuse treatment focus (15) and lack of cost data (12). A CASP checklist was completed for these 16 publications to assess quality.…”
Section: Resultsmentioning
confidence: 99%
“…During the period included in this systematic review, three publications 11,13,14 14 The costs of opioid misuse and abuse are significant. In this review, we found the highest mean annual costs per opioid abuser were among the publicly funded programs: VA population ($28,882; 1 study), followed by the Medicaid population ($25,140; 2 studies) and commercial population ($22,916; 5 studies).…”
Section: Societal Costsmentioning
confidence: 99%
“…CDC searched for evidence on opioid therapy compared with other treatments; costs of misuse, abuse, and overdose from prescription opioids; and costs of specific risk mitigation strategies (e.g., urine drug testing). Yearly direct and indirect costs related to prescription opioids have been estimated (based on studies published since 2010) to be $53.4 billion for nonmedical use of prescription opioids (170); $55.7 billion for abuse, dependence (i.e., opioid use disorder), and misuse of prescription opioids (171); and $20.4 billion for direct and indirect costs related to opioid-related overdose alone (172). In 2012, total expenses for outpatient prescription opioids were estimated at $9.0 billion, an increase of 120% from 2002 (173).…”
Section: Resource Allocationmentioning
confidence: 99%
“…Although poisoning is the most common cause of attempted self-harm [2], the majority of poisonings are unintentional [1]. In particular, rates of opioid poisoning and associated mortality have increased in the last three decades, making up approximately 40 % of drugrelated deaths and contributing to the overall healthcare and human costs of these poisonings [1,3].…”
Section: Introductionmentioning
confidence: 99%